Pengembangan Infrastruktur Pembelajaran Daring Menggunakan Antena Unidirectional - Rufman Akbar; Chaerul Anwar; Johannes Hamonangan Siregar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Situation during COVID19 pandemic, requires all schools to conduct online learning. This condition is done to prevent the spread of pandemic. The problem is that the infrastructure is not fully supported. Learning in marginal areas is still constrained by the difficulty of the signal or internet connection. This research was conducted to obtain an infrastructure design that can be used in areas with minimal internet connection, or even no internet network connection. Using R&D, the research begins by designing a network device on the school side – Acces Point, also a tool to expand coverage - repeater. Furthermore, design and testing of signal amplifier antennas that can be used on the client side is carried out. For the client side, several types of amplifier antennas are made that can be used to receive Wifi frequencies. There are three types of antennas that are made and tested, namely Yagi, Yagi Cross, and cantennas. Both are Unidirectional antenna. Connection quality is measured with a Wifi analyzer device to determine network quality. As for mobile phones, it is measured using the Wifi Master Key. The result obtained is a WELAN infrastructure design which is equipped with unidirectional antenna design with a total range of 8 Km.